Efficient Cu-catalyzed intramolecular O-arylation for synthesis of benzoxazoles in water. Issue 24 (7th April 2020) - Tang, Yanling; Li, Minxin; Gao, Hui; Rao, Gaoxiong; Mao, Zewei
Abstract : An efficient method was developed for synthesis of benzoxazoles by Cu-catalyzed intramolecular O -arylation of o -halobenzanilides in water. Abstract : An efficient method was developed for synthesis of benzoxazoles by Cu-catalyzed intramolecular O -arylation of o -halobenzanilides in water. This strategy provides several advantages, such as high yields, water as a green solvent and functional groups tolerance.